Livros didáticos e a matemática do ginásio: um estudo da vulgata para a reforma Francisco Campos - Pires, Inara Martins Passos (2004)
This study analyses how Mathematics, as a school subject, developed itself within the first years of its creation, from the so-called Francisco Campos Reform, in 1931. Based on the ideas of academics such as André Chervel and Roger Chartier, among others, the study intends to answer the following question: How Brazilian school books, which have been written after the Francisco Campos Reform, organized and stabilized the Mathematics as a subject, which was created from the fusion of Arithmetic, Algebra, and Geometry. The answer to such a question points towards the appropriation of the official text, which reveals to us incorporations of the project of globally restructuring the teaching of Mathematics from the heuristic method